2018
DOI: 10.1002/jbmr.3481
|View full text |Cite
|
Sign up to set email alerts
|

Normative Standards for HRpQCT Parameters in Chinese Men and Women

Abstract: Assessing bone architecture using high-resolution peripheral quantitative computed tomography (HRpQCT) has the potential to improve fracture risk assessment. The Normal Reference Study aimed to establish sex-specific reference centile curves for HRpQCT parameters. This was an age-stratified cross-sectional study and 1072 ambulatory Chinese men (n = 544) and women (n = 528) aged 20 to 79 years, who were free from conditions and medications that could affect bone metabolism and had no history of fragility fractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…A study from HK using the first-generation HR-pQCT found results similar to ours, suggesting that race may actually play a more prominent role compared with technical aspects of the machine itself. (17) In general, we found that HR-pQCT parameters differed by sex, age period (before versus after 50 years of age), site (tibia versus radius), and bone compartment (trabecular versus cortical bone). After the age of 50 years, greater age-related differences were observed in radial parameters compared with tibial parameters among both men and women.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…A study from HK using the first-generation HR-pQCT found results similar to ours, suggesting that race may actually play a more prominent role compared with technical aspects of the machine itself. (17) In general, we found that HR-pQCT parameters differed by sex, age period (before versus after 50 years of age), site (tibia versus radius), and bone compartment (trabecular versus cortical bone). After the age of 50 years, greater age-related differences were observed in radial parameters compared with tibial parameters among both men and women.…”
Section: Discussionmentioning
confidence: 69%
“…In these parameters, a higher value indicates poorer structural trait and, therefore, decline. (9,10,16,17) Across progressively older age groups, we observed increases in Ct.Po, Ct.Pm, Tt.Ar, Tb.Ar, Tb.Sp, Tb.Inhomogeneity and decreases in volumetric BMD, Ct.Ar, Ct.Th, Tb.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations